2566. Diagnosis of Pneumocystis jiroveci Pneumonia in HIV-Negative Immunocompromised Patients: Is the Gomori-Methenamine Silver Stain of Bronchoalveolar Lavage Fluid the Gold Standard or Sub-Standard?. (26th November 2018) - Slotkin, Rebecca; Abi-Raad, Rita; Liu, Yuehong; Grant, Matthew; Malinis, Maricar; Azar, Marwan M
Abstract: Background: Direct visualization of Pneumocystis jiroveci on bronchoalveolar lavage (BAL) fluid using the Gomori-methenamine-silver (GMS) stain historically has been the mainstay of diagnosis for P. jiroveci pneumonia (PJP), with studies from the early HIV/AIDS era reporting sensitivities of 90–95%. However, the burden of P. jiroveci organisms in BAL fluid is significantly lower in HIV-negative immunocompromised patients compared with HIV-positive patients with PJP, raising concerns that the BAL GMS stain is less sensitive in this population. Methods: We conducted a retrospective observational study at Yale-New Haven Hospital from 2012 to 2018, using electronic medical record chart reviews, to identify patients who underwent bronchoscopy with BAL GMS stain for the diagnosis of PJP. We collected additional patient factors such as age, sex, HIV status, and immunosuppressed status. For patients with a negative BAL GMS stain, we collected data on other diagnostics, including positive GMS lung biopsies, positive PJP PCR or DFA, and elevated serum (1–3)-β-d -glucan levels. We defined BAL GMS-negative cases as proven or probable based on investigator generated criteria (see Figure 1). Results: We identified 52 patients with PJP who received a BAL GMS stain, including 28 HIV-positive and 24 HIV-negative cases. Of 24 HIV-negative cases, 11 had BAL GMS-positive PJP and 13 had BAL GMS-negative PJP (9 proven and 4 probable). In the latter group, 6 had hematologic malignancies (HM), 2 had solid-organ transplants (SOT), 1 had hematopoietic stem cell transplant, 2 had SOT plus HM, and 2 received high-dose steroids. Proven diagnoses were made by GMS-positive lung biopsy ( n = 6), DFA ( n = 2), and PCR ( n = 1). Elevated (1–3)-β-d -glucan was observed in 7 of 8 cases (median: >500 pg/mL; range 39 to >500). Three patients developed adverse outcomes (1 readmission due to untreated PJP and 2 treatment delays). BAL GMS sensitivity for HIV-negative patients was 11/24 (46%) vs. 28/28 (100%) in HIV-positive patients. Conclusion: The sensitivity of BAL GMS for PJP is poor in HIV-negative immunocompromised patients. Missed cases or delayed treatment for PJP may lead to adverse outcomes. In HIV-negative patients with a clinical syndrome compatible with PJP, a negative BAL GMS does not rule out PJP and must be confirmed by supplementary diagnostics. Disclosures: All authors: No reported disclosures.